THE INFLUENCE OF TYPE OF MANURE AND DOSAGE OF PADDY ASH WASTE TOWARDS THE YIELD OF MUSTARD ON VERTISOL LAND - Priyono Sarwon (Universitas Islam Batik Surakarta, 2014)
Mustard plant is one of the favorite Indonesian vegetables population, because there are several benefits such as: blood booster drug protein, facilitates digestion, increase nutrient in the human body. The research aims at knowing the influence of type of manure and dosage of paddy ash waste towards the yield of mustard on vertisol land.The method is factorial experiment by usingrandomized completedesign with a range of manure treatment (4 kinds of animal manure: cow, goat, chicken and bird) and dosage ofpaddy ash waste (3 levels: a dose of 0 kg; 0.5 kg; and 1.0 kg). As the result,type of treatment on manure effect on plant height, number of leaves, fresh weight consumption, plant fresh weight, and plant dry weight contribute no effect on harvest index. While the dose treatment of paddy ash waste give effect on the number of leaves, fresh weight consumption, and plantdry weightand there is no effect on plant height, plant fresh weight and harvest index. The treatment between the range oflivestock manure and paddy ash wastein dosagecaused the different effect on the number of leaves, plant fresh weight and in fact, there is no effect on plant height, fresh weight consumption, plant dry weight,and harvest index. Various types of good manure for mustard cropin this research are animal manure:goat,chicken and bird and the dosage of paddy ash waste should be 0.5 kg/polybag.